Analysis of a Permanent-Magnet Brushless DC Motor with Fixed Dimensions - Brakanskis, Uldis; Dirba, Janis; Kukjane, Ludmila; Drava, Viesturs (Electrical, Control and Communication Engineering, 2010)
The purpose of this paper is to describe the analysis of a permanent-magnet brushless DC motor with fixed outer diameter and active zone length. The influence of air gap, material of permanent magnets and their size on the magnetic flux density of the machine and magnetic flux is analyzed. The work presents the calculations of two programs, the comparison of the results and the most suitable combination of factors that has been found.